Patients with Active Acromegaly are at High Risk of 25(OH)D Deficiency - Halupczok-Żyła, Jowita; Jawiarczyk-Przybyłowska, Aleksandra; Bolanowski, Marek (Frontiers in Endocrinology, 2015)
Acromegaly is a chronic disease characterized by hypersecretion of growth hormone (GH) and insulin-like growth factor 1 (IGF-1). Electrolyte disturbances such as hypercalcemia and hyperphosphatemia are reported in patients with this disorder. There is limited data on vitamin D status in subjects with acromegaly. The aim of the study was to determine calcium, inorganic phosphate, magnesium, alkaline phosphatase and 25(OH)D levels with regard to the activity of the disease. We also studied correlations of 25(OH)D and IGF-1, GH, body mass, body mass index and age. A study group consisted of 55 acromegalic patients, and was divided into three subgroups: active acromegaly (AA), well-controlled acromegaly (WCA), cured acromegaly (CA). We enrolled 29 healthy subjects to a control group (CG). Vitamin D deficiency was recorded in all AA patients, 13 WCA patients (92.86%), 10 CA patients (62.5%) and 13 controls (54.17%). The highest 25(OH)D levels were found in the CG group and the lowest in the AA group (p=0.012). The dose of octreotide did not influence serum 25(OH)D levels. A significant positive correlation between IGF-1 and 25(OH)D levels was observed in the AA group (r=0.58, p=0.024). Inorganic phosphate levels were the highest in the AA group. In conclusion, active acromegalic patients have lower 25(OH)D levels in comparison with the control group and are at higher risk of vitamin D deficiency.